PERSEPSI ORANG TUA MURID SEKOLAH DASAR NEGERI 18 TUBUNG TERHADAP KEBIJAKAN PEMERINTAH KABUPATEN MELAWI MELIBURKAN SEKOLAH PADA MASA PANDEMI COVID-19 - Suci Hidayati; Septian Peterianus; Waridah Waridah (Bestari: Jurnal Pendidikan dan Kebudayaan, 2021)
Abstrack. This research aims to find out and describe the Perceptions of Parents of 18Elementary Public Elementary Schools Regarding the Melawi Regency Government'sPolicy to Close Schools in the Covid-19 Pandemic Period and to produce a study on thePerceptions of Parents of 18 Primary Schools Regarding the Government of the MelawiRegency Government Restoring Schools during the Covid-19 Pandemic Period. Theresearch was carried out based on research background, namely the Circular of theMinister of Education and Culture No. 4 of 2020 regarding the implementation ofeducational policies in the emergency period of the spread of Covid-19 which requiredall schools including elementary schools to be closed or study at home. Therefore it makesthe teaching and learning process not as usual because the teaching and learning processis closed or learning at home so that there are obstacles that are felt by students such asoften feeling bored, and not concentrating. There are also constraints felt by students'parents such as the constraints in dividing time watching children study with work timeduring government policy to close school or having to study at home during the Covid19pandemic.ThisstudyusesdescriptivequalitativeresearchwithavarietyofGroundedtheoryapproaches.ThesubjectofthisstudyistheParentsof18TubungNegeriPrimarySchoolPupils, Labang Village, Belimbing Belimbing District, Melawi Regency with 9parents of 1 pupils, 18 Tubung Public Elementary School teachers. Data collectiontechniques using observation, interviews, and documentation. The instrument used wasthe interview sheet.The results of this study describe the results of interviews with parentsabout the Perceptions of Parents of 18 Elementary School Public Schools Regarding theGovernment of Melawi District Government Closed School in the Covid-19 PandemicPeriod. It can be seen that there are different and varied opinions of the parents ofstudents. Some parents agreed, but some did not agree or criticize the Melawi Regency Government’s policy of dismissing the School during the Covid-19 pandemic.Keywords: Parents' Perception of Students, Government Policy, Covid-19 Pandemic. Abstrak. Penelitiaan ini bertujuan untuk mengetahui dan mendeskripsikan PersepsiOrang Tua Murid Sekolah Dasar Negeri 18 Tubung Terhadap Kebijakan PemerintahKabupaten Melawi Meliburkan Sekolah Pada Masa Pandemi Covid-19 danMenghasilkan sebuah penelitian tentang Persepsi Orang Tua Murid Sekolah Dasar Negeri18 Tubung Terhadap Kebijakan Pemerintah Kabupaten Melawi Meliburkan Sekolah padaMasa Pandemi Covid-19. Penelitian dilaksanakan berdasarkan latar belakang penelitian, yaitu adanya surat edaran Menteri Pendidikandan kebudayaan Nomor 4 tahun 2020tentang pelaksanaan kebijakan pendidikan dalam masa darurat penyebaran Covid-19yang mengharuskan semua sekolah termasuk Sekolah Dasar diliburkan atau belajardirumah. Maka dari itu membuat proses belajar mengajar tidak seperti biasaanya karenaproses belajar mengajar diliburkan atau belajar dirumah sehingga terdapat kendala yangdirasakan murid seperti sering merasa bosan, dan tidak berkonsentrasi. Juga terdapatkendala yang dirasakan orang tua murid seperti kendala dalam membagi waktumengawasi anak belajar dengan waktu bekerja selama kebijakan pemerintah meliburkansekolah atau harus belajar dirumah pada masa pandemi Covid-19. Penelitian inimenggunakan penelitian kualitatif deskriptif dengan variasi pendekatan Groundedtheory. Subjek penelitian iniorang tua murid Sekolah DasarNegeri 18 Tubung DesaLabang Kecematan Belimbing Kabupaten Melawi dengan jumlah 9 orang tua murid 1guru Sekolah Dasar Negeri 18 Tubung. Teknik pengumpulan data menggunakan teknikobservasi, wawancara, dan dokumentasi. Instrumen yang digunakan yaitu lembarwawancara. Hasil penelitian ini adalah mendeskripsikan hasil wawancara dengan orangtua murid tentang persepsi orang tua murid Sekolah Dasar Negeri 18 Tubung terhadapkebijakan pemerintah kabupaten melawi meliburkan sekolah pada masa pandemi Covid19.Dapat diketahuibahwaorangtuamuridsetujudanadapulayangtidaksetujuterhadapkebijakanPemerintah Kabupaten Melawi meliburkan Sekolah pada masa pandemiCovid-19.Kata kunci : Persepsi Orang Tua Murid, Kebijakan Pemerintah, Pandemi Covid-19.